Region of Yeast TAF 130 Required for TFIID To Associate with Promoters - Mencía, Mario (American Society for Microbiology, 2001)
TFIID, a multiprotein complex comprising the TATA-binding protein (TBP) and TBP-associated factors (TAFs), associates specifically with core promoters and nucleates the assembly the RNA polymerase II transcription machinery. In yeast cells, TFIID is not generally required for transcription, although it plays an important role at many promoters. Understanding of the specific functions and physiological roles of individual TAFs within TFIID has been hampered by the fact that depletion or thermal inactivation of individual TAFs generally results in dissociation of the TFIID complex. We describe here C-terminally deleted derivatives of yeast TAF130 that assemble into normal TFIID complexes but are transcriptionally inactive in vivo. In vivo, these mutant TFIID complexes are dramatically reduced in their ability to associate with all promoters tested. In vitro, a TFIID complex containing a deleted form of TAF130 associates poorly with DNA, but it is unaffected for interacting with transcriptional activation domains. These results suggest that the C-terminal region of TAF130 is required for TFIID to associate with promoters.